Сучасний стан та структура ценопопуляцій видів роду Fritillaria L. у деяких місцезнаходженнях Полтавської області - Didenko, I.P.; Stetsyuk, N.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The results of the investigation of chorology, ecological and coenotic features, a state of populations of species of Fritillaria L. genus in terrain of the Poltava Region are presented. The recommendations on preservation of a genus are given.